(untitled) (International Conference on Computers in Education, 2023)
This paper examines the requirements for creating a local safe map, which is the core of regional disaster prevention, through a case study in a historical local city in Japan. Amid the rising awareness of disaster prevention, efforts are being made in various places to voluntarily create disaster prevention maps through town walks. It is expected to improve residents’ awareness of disaster prevention, improve local disaster prevention capabilities, and revitalize local communities. What are the requirements for a local safety map creation to continue to play a central role in regional disaster prevention rather than being a temporary event? Based on our past experiences, we review our research activity what is necessary to make such map-making the core of regional disaster prevention. The following is findings through our experience in the map-making activities. Sustainable development is possible by making it a regular activity in the district rather than a one-off event. Sharing of subjective information in cooperation with the disaster prevention division leads to improve reliability of information by consensus with the members and revitalization of activities through workshops. it is also necessary to select media that provide information from the user’s perspective.